Calcium Dynamics in Dendrites of Hippocampal CA1 Interneurons in Awake Mice - Francavilla, Ruggiero; Villette, Vincent; Martel, Olivier; Topolnik, Lisa (Frontiers in Cellular Neuroscience, 2019)
Hippocampal inhibitory interneurons exhibit a large diversity of dendritic Ca2+ mechanisms that are involved in the induction of Hebbian and anti-Hebbian synaptic plasticity. High resolution imaging techniques allowed examining somatic Ca2+ signals and, accordingly, the recruitment of hippocampal interneurons in awake behaving animals. However, little is still known about dendritic Ca2+ activity in interneurons during different behavioral states. Here, we used two-photon Ca2+ imaging in mouse hippocampal CA1 interneurons to reveal Ca2+ signal patterns in interneuron dendrites during animal locomotion and immobility. Despite overall variability in dendritic Ca2+ transients across different cells and dendritic branches, we report consistent behavior state-dependent organization of Ca2+ signalling in interneurons. As such, spreading regenerative Ca2+ transients dominated in dendrites during locomotion, whereas both spreading and localized Ca2+ signals were seen during immobility. Thus, these data indicate that while animal locomotion is associated with widespread Ca2+ elevations in interneuron dendrites that may reflect regenerative activity, local Ca2+ transients that may be related to synaptic activity become apparent during animal quiet state.